The Impact of Health Education with Demonstration Methods and Video Animation on Santriwati Constitution in Yogyakarta IT Building School - Rabani, Athaya Jahra; Yusniarita, Yusniarita; Prayogi, Agus Sarwo (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Breast cancer ranks first in Indonesia with the highest incidence of cancer and is the leading cause of cancer deaths. One of the causes of breast cancer has increased due to the lack of education about SADARI (Breast Self Examination) during adolescence for early detection of breast cancer, so that the knowledge that adolescents have about health is very minimal and can cause a lack of concern or insensitivity to a symptom of a disease that arises abnormally in the body, so health promotion is needed in an effort to increase knowledge related to SADARI. Health promotion in adolescent girls will be more interesting if it is carried out with various methods such as demonstrations and showing videos. Objective: Knowing the difference in knowledge improvement between demonstration methods and animated videos in SADARI health education for female students. Methods: This type of research is a quantitative study with Quasi Experiment, Non-Equivalent with Control Group Design which was conducted from February to March 2023. The population female students of class X, XI, XII Natural Science and Social Science at SMA IT Bina Umat Yogyakarta. The technique of taking samples with proportionate stratified random sampling. Results: Wilcoxon test in the experimental group obtained p value = 0.000 and in the control, group obtained p value = 0.000. Mann Whitney test in the experimental and control groups after the intervention obtained p value=0.025. Conclusion: There is a difference between the demonstration method and the animated video to the increased santriwati knowledge of SADARI with a value of p=0.025 (p<0.05). The demonstration method makes the teaching clearer and more concrete and focuses the attention of the student as well as better directs the student's learning process to the materials being studied.